Phase transition sequences in tetramethylammonium tetrachlorometallates by X‐ray diffraction and spectroscopic measurements. Issue 5 (2nd August 2017) - Binns, Jack; McIntyre, Garry J; Barreda-Argüeso, José A.; González, Jesús; Aguado, Fernando; Rodríguez, Fernando; Valiente, Rafael; Parsons, Simon
Abstract : Structures and phase sequences for two tetramethylammonium tetrachlorometallate compounds have been determined as a function of temperature. Crystal‐packing analysis and first‐principles calculations were used to rationalize the experimentally determined sequence. Abstract : The phase transition sequences of two members of the tetramethylammonium tetrachlorometallate(III) family of hybrid organic–inorganic salts have been determined and structurally characterized as a function of temperature for the first time. Unusually, a reduction in point‐group symmetry with increasing temperature until reaching a cubic prototype phase is observed. Two additional intermediate phases are observed for Fe 3+ . First‐principles calculations and the presence of short Cl…Cl contacts for Ga 3+ suggest the [GaCl4 ] − anion to be conformationally hindered due to stronger lone‐pair–σ‐hole interactions. The conformationally more flexible Fe 3+ structures show sublattice melting with the onset of rotational disorder in the [NMe4 ] + cations occurring 40 K below the corresponding onset of rotational disorder in the [FeCl4 ] − sublattice.